Intervenciones de enfermería en un paciente con hemorragia digestiva alta por cirrosis hepática - Pinta Tuitise, Adriana Maricela (2024)
The purpose of this study was to carry out nursing interventions in a patient with upper gastrointestinal bleeding due to liver cirrhosis, focusing on early identification, effective management, prevention of complications to achieve prompt recovery, addressing a clinical situation of extreme relevance. in the field of nursing and medicine. Liver cirrhosis, a chronic disease that seriously affects liver function, is the context in which this 56-year-old patient develops, who was admitted to the emergency area due to upper digestive bleeding. The importance of this study lies in the severity of upper gastrointestinal bleeding, a potentially fatal complication of liver cirrhosis. Nursing staff faced the challenge of providing comprehensive and urgent care, including blood transfusions, constant monitoring of vital signs, preparation for endoscopic procedures. This study contributes significantly to knowledge in the field of nursing, underlining the importance of nursing's role in improving the quality of life of patients, as well as in preventing serious complications. Providing a solid basis for clinical decision making and implementation of more effective care strategies in patients with liver cirrhosis and upper gastrointestinal bleeding. Interdisciplinary collaboration, constant updating of nursing practices stand out as essential elements to guarantee optimal care, as well as the successful recovery of these patients.